2014
DOI: 10.1002/ceat.201400235
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Agglomeration Characteristics of the Residue from Corn Stalk‐Based Cellulosic Ethanol

Abstract: Lignocellulose is considered an efficient raw material to produce fuel ethanol. Clean utilization of the solid residue derived from lignocellulose‐based fuel ethanol is important for the biomass‐to‐ethanol production chain. Combustion characteristics of the residue originating from corn stalk‐based cellulosic ethanol are studied in a circulating fluidized bed. Results indicate that circulating fluidized‐bed combustion is an effective and stable way to burn the residue with high moisture content. CO emission du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Corn stalk can be used to produce furfural and fermentable glucose for bioethanol production, which greatly reduces the reliance on fossil fuels in bioethanol production. Moreover, it is beneficial for environmental protection and sustainable development [17][18][19][20][21]. It was found that the hard reticular structure of corn straw lignin is the main issue that hinders the conversion of straw into biofuels [22].…”
Section: Introductionmentioning
confidence: 99%
“…Corn stalk can be used to produce furfural and fermentable glucose for bioethanol production, which greatly reduces the reliance on fossil fuels in bioethanol production. Moreover, it is beneficial for environmental protection and sustainable development [17][18][19][20][21]. It was found that the hard reticular structure of corn straw lignin is the main issue that hinders the conversion of straw into biofuels [22].…”
Section: Introductionmentioning
confidence: 99%